Criminal Policy to Treat Delices Against Religion and Beliefs Harmony - Royani, Yayan Muhammad (Universitas Islam Negeri Walisongo Semarang, 2021)
The protection of the rights to freedom of religion and belief in the constitution aims to create a community life based on morals based on divinity. As a country with a high level of plurality from the aspects of religion and belief, protection of religious harmony and belief is necessary to achieve this goal. Based on the above points of thought, several problems can be formulated, namely how is the current criminal policy in overcoming offenses against religious and belief harmony. And what will the future criminal policy be in overcoming offenses against religious harmony and belief. The method used in this research is a normative juridical approach, where the data used are secondary sources in the form of primary legal materials, secondary legal materials and tertiary legal materials.This research is a descriptive analytical study, namely research to describe the problem, analyze the problem and classify the problem for research purposes which are presented descriptively. The results of this study indicate that the criminal acts formulated in the Criminal Code are very limited, including not protecting beliefs protected by the constitution and there is still a divergence by including religious offenses in the Chapter on Public Order. In the non-penal policy, the regulations governing religious harmony are still ineffective and the current government is not serious about creating harmony between religious and believers. Future penal efforts can be made by updating the Criminal Code. As an effort to improve, the concept of the Criminal Code can formulate the provisions of offenses by looking at the provisions of offenses contained in the Draft Law on Religious Harmony. In non-penal efforts, the approach is through the formulation and implementation of government programs. Among them are approaches to understanding theology, education, dialogue and conflict resolution.Perlindungan atas hak kebebasan beragama dan berkepercayaan dalam konstitusi bertujuan supaya tercipta kehidupan masyarakat yang berlandaskan moral atas dasar ketuhanan. Sebagai negara dengan tingkat pluralitas yang tinggi dari aspek agama dan kepercayaan, maka perlindungan terhadap kerukunan umat beragama dan berkepercayaan mutlak dibutuhkan untuk mencapai tujuan tersebut. Berdasarkan pokok pemikiran di atas, maka dapat dirumuskan beberapa permasalahan, yaitu bagaimanakah kebijakan kriminal saat ini dalam menanggulangi delik-delik terhadap kerukunan umat beragama dan berkepercayaan. Dan bagaimanakah kebijakan kriminal yang akan datang dalam menanggulangi delik-delik terhadap kerukunan umat beragama dan berkepercayaan. Metode yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif, dimana data yang digunakan adalah sumber sekunder berupa bahan hukum primer, bahan hukum sekunder maupun bahan hukum tersier. Adapun penelitian ini merupakan penelitian deskriptif analitis, yaitu penelitian untuk mendeskripsikan masalah, menganalisis masalah dan mengklasifikasi masalah untuk kepentingan penelitian yang disajikan secara deskriptif. Hasil dari penelitian ini bahwa tindak pidana yang dirumuskan dalam KUHP sangatlah terbatas, diantaranya belum melindungi kepercayaan yang dilindungi konstitusi serta masih terdapat divergensi dengan memasukan delik agama dalam Bab Ketertiban Umum. Dalam kebijakan non penal, regulasi yang mengatur tentang kerukunan umat beragama masih kurang efektif serta pemerintah saat ini tidak serius menciptakan harmonisasi antar umat beragama dan berkepercayaan. Upaya penal yang akan datang dapat dilakukan dengan pembaharuan KUHP. Sebagai upaya penyempurnaan, Konsep KUHP dapat memformulasikan ketentuan delik dengan melihat ketentuan delik yang terdapat dalam RUU Kerukunan Umat Beragama. Dalam upaya non penal, pendekatan melalui penyusunan dan pelaksanaan program pemerintah. Diantaranya dengan pendekatan pemahaman teologi, pendidikan, dialog dan resolusi konflik.